Persepsi Komitmen Manajemen Sebagai Prediktor : Komitmen Afektif Dan Prestasi Kerja Sebagai Konsekuensi - Riza Indah Rifanti; Jajuk Herawati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
This study aims to examine the variables of management commitment, affective commitment and work performance with affective commitment as a mediating variable. This study took a sample from on of company which is located in Yogyakarta. The sampling of this research using nonprobability sampling method with sampling twchnique namely saturated sampling or census. The sample data collection was carried out by distributing questionnaires with the help of the Google Form Link and them distributed through the employeeâ€™s WhatsApp number. This research data processing using multiple linier regression analysis technique then assisted by the program SPSS Fot Windows Version 17.0.  The Results  in this study are: there  is a positive influence from the variabel Management Commitment to Affective Commitment; there is a positive influence from the Affective Commitment on the Job Performance variable; there is a positive influence from the Management Commitment variable on the Job Performance variable; and there is an insignificant (negative) result of the perception of Management Commitment variable on Job performance as a consequence throughh the Affective Commitment variable as the mediating variable. Suggestions fot further research can choose other mediating variables to determine the extent to which work performance can be affected